The law and practice of banking, collateral securities, and mortgages - Olulana, O. J .A. (Lagos : Diversities Enterprises, 2000)
The Author discusses generally the business itself an delved further into the legal aspects of banker-customer relationship highlighting the contractual nature of the relationship. He went further to discuss bonds, bills of sale, securities for bank lending and mortgages.
Includes bibliographical references.
ne 28/07/2021
Loans
Keywords: Securities; Banking law; Banks and banking; Nigeria